Programas televisivos en el comportamiento de los niños de Cuarto año de Educación General Básica de la Escuela Fiscal "Riobamba" de la parroquia Guamaní, cantón Quito, provincia de Pichincha en el año lectivo 2016-2017. - Semblantes Changoluiza, Myriam Jeanneth (2018)
In this project, we know about the behavioral changes generated by television programs that are of concern to society today. Nowadays it is easy to visualize that the majority of families have a television at home and therefore there are the majority of children who are exposed to television and influences, whether positive or negative. Watch over TV shows that have no meaning or values cause serious problems in the behavior of children, from this point is where according to experts originate the changes of behavior, aggressiveness, rebellion and disrespect inside and outside the educational establishment. Parents for various reasons did not have control over television programs and the number of hours their child spent on television, so children have access to a large number of programs and series not recommended for their age, causing a change of behavior in children. In view of the problem that exists today, we have taken this example to be able to realize the project. To carry out the present project, the main tool was the surveys of teachers, students and parents of the "Riobamba" school.